Downward Accountability of World Vision Ghana in Saboba District - Langnel, Z. (University of Ghana, 2015)
Non-Governmental Organizations (NGOs) have become major players in Community Development Agenda and perform intermediary roles between donors and intended beneficiaries. Unfortunately, highly publicized corruption scandals are discovered in literature often associated with the activities of NGOs especially in developing countries. To sanitize the aid delivery chain, NGOs are required to be accountable to donors (upward accountability) and beneficiaries (downward accountability). However, over dependence on upward accountability have failed to produce the desired results owing to the fact that donors are remotely located amidst weak regulatory frameworks in developing countries, thus, making it extremely difficult to ensure effective accountability of NGOs. It is against this backdrop that this study was qualitatively conducted through the lens of an interpretive research paradigm. Three participatory models (i.e Arnstein‟s ladder of participation, Vernooy‟s framework of participation, and White‟s typology of participation) were adopted to investigate the extent to which NGOs involve beneficiaries across the three stages of a project life cycle – planning/decision, implementation and evaluation stages. Data were collected through in depth interviews and documentary reviews. In all, 21 interviews and 5 FGDs were conducted in five beneficiary communities. The study discovered generally that downward accountability of the studied NGO was rhetorical. The findings suggest that participation at the planning stage was tokenistic as the project‟s goals and objectives were formulated long before the NGO got into the communities. Though the implementation stage recorded the highest involvement of beneficiaries, it was quite exploitative as the NGO might have used beneficiaries‟ free labor to achieve project‟s cost effectiveness. The evaluation stage recorded the lowest involvement of beneficiaries across the three stages. Thus, participatory review meetings were not held to rigorously review the success of the project. As a result, beneficiaries were not empowered to be the main drivers of their own development.
Thesis (MPhil) - University of Ghana, 2015